(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
Bone regeneration is a critical factor for the long-term success of dental implant therapy, particularly in patients with insufficient alveolar bone volume. Recent advances in biomaterial science have led to the development of innovative materials designed to enhance bone healing and osseointegration around dental implants. This article reviews modern biomaterials used in bone regeneration, including bioactive ceramics, polymers, composites, and bone graft substitutes. Special attention is given to their biological properties, mechanisms of action, and clinical effectiveness. Current research indicates that modern biomaterials significantly improve bone regeneration outcomes by promoting osteoconduction, osteoinduction, and biocompatibility. The findings highlight the importance of material selection in implant dentistry and emphasize the potential of advanced biomaterials to improve implant stability and long-term clinical success.